Gokarneshwara or Bisaldeo Temple - Temples of India Project Team (Jio Institute, 2024)
The Gokarneshwara or Bisaldeo Temple is situated in a courtyard near the Bisalpur dam, on the banks of the Banas River. The temple’s architectural layout includes a garbhagriha (sanctum sanctorum), an antarala (vestibule or antechamber), a mahamandapa (pillared hall) with lateral transepts and an ardhamandapa (partially enclosed hall). It is a nirandhara prasada, meaning it lacks the pradakshina path or circumambulatory path. The sanctum is pancharatha (consisting of five projections on each side) on plan, and its walls are plain in design.